2018
DOI: 10.1088/1757-899x/288/1/012102
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Advantage: Mediator of Diversification and Performance

Abstract: Abstract. Study relates to the correlation between diversification strategy and corporate sustainability performance, many of them are conducted in service industry. In this study, it is explained about competitive advantage that also becomes the important attention on the creation of corporate sustainability performance. But study relates to mediating effect of competitive advantage on the correlation of diversification and corporate sustainability performance, has not reviewed especially in-service industry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
2
0
2
Order By: Relevance
“…Human capability is part of an organisation’s valuable assets to gain competitive advantage (Kamboj & Rahman, 2017 ). Most importantly, the capability to strategically meet customers’ needs ensures customer satisfaction, which is important for halal SMEs in their efforts to gain competitive advantage and sustainability (Sihite, 2018 ). Moreover, Correia et al ( 2020 ) confirmed the mediating role of competitive advantage in the relationship between dynamic capability and business sustainability.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Human capability is part of an organisation’s valuable assets to gain competitive advantage (Kamboj & Rahman, 2017 ). Most importantly, the capability to strategically meet customers’ needs ensures customer satisfaction, which is important for halal SMEs in their efforts to gain competitive advantage and sustainability (Sihite, 2018 ). Moreover, Correia et al ( 2020 ) confirmed the mediating role of competitive advantage in the relationship between dynamic capability and business sustainability.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Bersaing dan Kinerja Industri Kreatif Banyak penelitian yang mengungkap bahwa keberhasilan peningkatan kinerja industri tergantung bagaimana industri tersebut menciptakan keunggulan bersaing dalam menghadapi kompetitor khususnya di pasar baru seperti halnya penelitian Rose et al (2010), Majeed (2011), Husnah et al (2013, Ghasemi et al (2015), Davcik & Sharma (2016), Aryana et al (2017) dan Sihite (2018). Keunggulan bersaing berpengaruh positif dan signifikan terhadap kinerja industri.…”
Section: G Hubungan Orientasi Pasar Inovasi Dan Kreativitas Produk unclassified
“…Hasil penelitian ini membuktikan bahwa keunggulan bersaing berpengaruh positif dan signifikan terhadap kinerja industri. Temuan ini memperkuat penelitian-penelitian terdahulu seperti penelitian Zhou et al (2009) Sihite (2018). Kondisi ini menunjukkkan bahwa keunggulan bersaing adalah kunci untuk kinerja bisnis jangka panjang bagi industri kreatif.…”
Section: G Keunggulan Bersaing Dan Kinerja Industriunclassified
“…Many manufacturers were unable to get up because the product research and development process was not running optimally. Diversification has a dominant impact on increasing competitive advantage (Sihite, 2018) .but research needs to be continued in the industrial sector automation system. In the banking sector, the diversification strategy has an important role in increasing competitive advantage (Wanjiru & Nzulwa, 2018).…”
Section: Em-2023-4876mentioning
confidence: 99%